THE PLANNING OF DRAINAGE SYSTEM OF TAWANG STATION TO TANJUNG MAS HARBOR - Wahyu Sejati; Christina Sari; Dina Paramitha Anggraeni Hidayat; Dewi Rintawati (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2024)
Freight transportation by rail is considered to be more time-efficient than road transportation. In response, the government has activated the freight rail line between Tawang Station and Tanjung Emas Port.Objectives: This study focuses on solving drainage system problems by designing a drainage channel.Methodology: This study uses hydrological and hydraulic calculations that are needed to get drainage design.Conclusion, Significance and Implication: The open space condition along the section of Stasiun Tawang – Pelabuhan Tanjung Emas from Km.0+275 to Km. 0+660 meets the standards ranging from 2.44 to 10.87 meters, while the standard used is 2.35 to 2.53 meters. Therefore, a drainage canal can be constructed. The results of the hydrological analysis show the planned flood discharge for 5-10 years. For 5 years, it is 0.906075 m³/sec, and for 10 years, it is 1.029242 m³/sec. The design for the new spillway includes trapezoidal and rectangular shapes. The trapezoidal design uses a cross-sectional width of 0.60 meters and a channel height of 0.70 meters, while the rectangular design uses a cross-sectional width of 0.80 meters and a channel height of 1.00 meters.